2018
DOI: 10.1007/s11856-018-1783-0
|View full text |Cite
|
Sign up to set email alerts
|

Zeta functions of alternate mirror Calabi–Yau families

Abstract: We prove that if two Calabi-Yau invertible pencils have the same dual weights, then they share a common factor in their zeta functions. By using Dwork cohomology, we demonstrate that this common factor is related to a hypergeometric Picard-Fuchs differential equation. The factor in the zeta function is defined over the rationals and has degree at least the order of the Picard-Fuchs equation. As an application, we relate several pencils of K3 surfaces to the Dwork pencil, obtaining new cases of arithmetic mirro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…The main aim of this paper is to generalize and to comment on a recent result of Doran, Kelly, Salerno, Sperber, Voight and Whitcher [8] on the zeta function of certain pencils of Calabi-Yau hypersurfaces. For a more extensive discussion on the history of this particular result we refer to the introduction of [8].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The main aim of this paper is to generalize and to comment on a recent result of Doran, Kelly, Salerno, Sperber, Voight and Whitcher [8] on the zeta function of certain pencils of Calabi-Yau hypersurfaces. For a more extensive discussion on the history of this particular result we refer to the introduction of [8].…”
Section: Introductionmentioning
confidence: 93%
“…In a recent preprint Doran, Kelly, Salerno, Sperber, Voight and Whitcher [8] showed the following result (using Dwork cohomology and some results on the Picard-Fuchs equation):…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Here we write µ n for the group of nth roots of unity. In previous work [DKSSVW17], we showed that these five pencils share a common factor in their zeta functions, a polynomial of degree 3 associated to the hypergeometric Picard-Fuchs differential equation satisfied by the holomorphic form. (Kloosterman [Klo17] has recently proven a more general version of this theorem, with a different approach.)…”
Section: Pencilmentioning
confidence: 99%